Mono‐ and Diruthenium, Symmetrical and Unsymmetrical Complexes Bridged by Pyrene Derivatives: Experimental and Theoretical Studies. Issue 33 (6th September 2017) - Zych, Dawid; Slodek, Aneta; Pająk, Michał; Krompiec, Stanisław; Spólnik, Grzegorz; Danikiewicz, Witold
Abstract : New mono‐ and diruthenium, symmetrical and unsymmetrical complexes, bridged by a new cyclometalating 1, 3, 6, 8‐tetra(4‐substituted‐2‐pyridyl)pyrene derivative containing the solubilizing group 2, 2‐dimethylpropyloxy, with the terminal 4′‐phenyl‐2, 2′:6′, 2′′‐terpyridine ligands containing diethylamine and a 2‐ethynyl‐9, 9‐dioctylfluorene moiety, were synthesized and thoroughly characterized. Thermal studies show that the obtained complexes retain high thermal stability. Spectroscopic studies show the metal‐to‐ligand charge‐transfer excitation. Further, electrochemical studies show delocalization of the electronic charge (mixed valance). In addition, density functional theory and time‐dependent density functional theory calculations have provided more detail about the structural properties and a deeper understanding of the experimental results. All of the obtained results show the considerable differences between the mono‐ and diruthenium and symmetrical and unsymmetrical complexes. Abstract : New ruthenium complexes, bridged by a cyclometalating 1, 3, 6, 8‐tetra(4‐substituted‐2‐pyridyl)pyrene derivative containing the solubilizing group 2, 2‐dimethylpropyloxy, have been synthesized and characterized. All results show considerable differences between symmetrical and unsymmetrical mono‐ and diruthenium complexes.